Invasive aspergillosis in children after haematopoietic stem cell transplantation - Styczyński, Jan; Gil, Lidia (Contemporary Oncology/Współczesna Onkologia, 2010)
A significant improvement has been observed in the results of therapy in haematological malignancies in children over the last three decades, related to intensification of therapy. However, it is followed by an increase of infections. Invasive fungal infections (IFI), including invasive aspergillosis (IA), are among the most life-threatening complications of intensive anticancer therapy. Children undergoing allogeneic haematopoietic stem cell transplan-tation (allo-HSCT) are at high risk of developing IA, especially after haploidentical or cord blood allo-HSCT as well as in congenital immu-nodeficiencies being treated with this method. Current prospective analyses indicate a change in epidemiology of IFI in the adult allo-HSCT setting, since IA (mainly Asper-gillus fumigatus) is diagnosed in about 60% of IFI. Risk factors for development of IA in children are: chronic graft- versus -host disease, steroid therapy 2 mg/kg/day or  60 mg/day over 10 days and age over 10 years. Favourable factors for IA course in children are haematological recovery and remission of malignancy. Current IA diagnostics is based on: conventional microbiological methods, serological assays (galacto-mannan, 1,3--D-glucan), molecular tests and radiology (mainly HRCT). Mortality in children with IA after allo-HSCT over the last decade was up to 75-90%. Currently, results of IA therapy are improving. This review presents updated definition and classifications of IA, as well as pharmacological strategies of antifungal prophylaxis and therapy. The characteristics and experience in use of antifungal drugs in IA in children are presented.